Vascularized Bone Grafts for Spinal Fusion—Part 1: The Iliac Crest. Issue 5 (22nd February 2021) - Reece, Edward M; Davis, Matthew J; Wagner, Ryan D; Abu-Ghname, Amjed; Cruz, Alex; Kaung, Geoffrey; Verla, Terence; Winocour, Sebastian; Ropper, Alexander E
Abstract: BACKGROUND: Iliac crest autograft has been the gold standard for harvest of fusion materials in spine surgery. The benefits of a vascularized version of this bone graft—including delivery of stem cells, ability to deliver antibiotics to the fusion bed, and relative ease of harvest—make this technique superior to free bone transfer in the achievement of augmented spinal fusion. OBJECTIVE: To present a brief summary of similar existing concepts before describing the novel technique of this vascularized posterior iliac crest bone graft. METHODS: Vascularized posterior iliac crest bone graft can be harvested from the same midline lumbar incision used for thoracolumbar spinal fusion, through lateral dissection around the paraspinals to the iliac crest. Recipient sites in the posterolateral bony spinal gutters may be as rostral as T12 and caudal as the sacrum. The ability to cover multiple lumbar levels can be achieved with desired lengths of the donor iliac crest. RESULTS: Over 14 vascularized iliac crest bone grafts have been performed to augment lumbar fusion for salvage after pseudoarthrosis. Operative time and bleeding are reduced compared to free flap procedures, and no patients have experienced any complications related to these grafts. Indocyanine green (ICG) angiography has been utilized in a novel way to ensure the vascularity of the bone graft prior to arthrodesis. CONCLUSION: While long-term follow-up will be required to fully characterize fusion rates and patient morbidity, this innovative surgical option augments spinal fusion in patients with, or at increased risk for, pseudoarthrosis.